Preparation and investigation of cobalt nanoparticles by laser ablation: Structure, linear, and nonlinear optical properties - Dayekh Manar. Lo.; Ghadi Amin; Hussain Saleem A. (Open Engineering, 2024)
In this study, cobalt nanoparticles (CoNPs) were prepared by using an Nd–YAG pulsed laser at a wavelength of 1,064 nm and an energy of 800 mJ. From the results of the structural and morphological attributes of CoNP films, it is evident that CoNPs exhibit different spherical configurations with diameters spanning from a few nanometers to 24 nm. The surfaces of these CoNP films indicate that they exhibit a certain degree of homogeneity and uniform vertical heights. Additionally, the results demonstrate an increase in granular size growth and the emptying of cavities on the material’s surface. The absorption curves appeared as a function of the wavelength within the range of 300–1,000 nm and the peak absorption of CoNPs in the ultraviolet radiation region, and the prohibited energy gap for direct transitions was known, and the value is 4 eV, while the nonlinear optical properties showed that the particles show a nonlinear refractive index (self-defocusing) and a nonlinear absorption cobalt coefficient with the absorption of two photons; thus, the CoNPs possess good nonlinear properties and can be used in nonlinear optical photonic device, optical power limiter, and a wide range of nonlinear applications.